Double-dose osimertinib combined with intrathecal injection of pemetrexed improves the efficacy of EGFR-mutant non-small cell lung cancer and leptomeningeal metastasis: case report and literature review - Zhong, Wenjuan; Wu, Longqiu; Huang, Lixing; Wang, Jianfeng; Shi, Huaqiu; Wu, Shugui (Frontiers in Oncology, 2024)
Leptomeningeal metastasis (LM) is a complication of non-small cell lung cancer (NSCLC) characterized by poor prognosis and short survival. A variety of therapeutic approaches have been sought to improve the efficacy of LM. Here we present a clinical case and conduct a literature review to investigate the effectiveness and safety of double-dose osimertinib combined with a pemetrexed intrathecal injection. This is an older man who underwent thoracoscopic pneumonectomy and was diagnosed with stage IIA lung adenocarcinoma with EGFR21 L858R mutation. He experienced thoracic vertebral metastases 33 months postoperatively and received first-line treatment with gefitinib combined with radiotherapy for vertebral metastases. However, the patient developed a grade 3 rash with unacceptable toxicity and his CEA levels were significantly increased 22 months later, leading to a targeted treatment adjustment to 80 mg of osimertinib orally once daily. Four months later, the patient developed LM and osimertinib dosage was increased to 160 mg once daily; however, neurological symptoms did not improve, and cerebrospinal fluid (CSF) tumor cells remained detected. Accordingly, the patient received an intrathecal injection of pemetrexed (dose 30 mg) every 2-3 months, 2-3 times per course (4-6 days each time), and continued to receive a double dose of osimertinib. After three courses of intrathecal chemotherapy, CSF tumor cells were eliminated, and neurological symptoms significantly improved. During the treatment, he experienced a one-degree rash, leukopenia, thrombocytopenia, and fatigue. This patient has been alive and well with disease control for 28 months since the diagnosis of meningeal metastases. Combining double-dose osimertinib and an intrathecal injection of pemetrexed demonstrated therapeutic efficacy and manageable adverse effects in this patient with advanced NSCLC with EGFR-mutant and LM.